ACTIONS DEVELOPED IN THE TERRITORY FOR USERS OF PSYCHOACTIVE SUBSTANCES: CARE IN FREEDOM? - Siqueira, Daiana Foggiato de; Zubiaurre, Priscila de Melo; Wasum, Fernanda Demetrio; Silveira, Júlia Oliveira; Marchiori, Mara Regina Caino Teixeira; Soccol, Keity Laís Siepmann (Cogitare Enfermagem, 2024)
Objective: To understand the care actions provided by health workers to users of psychoactive substances in the territory. Materials and Methods: Qualitative, descriptive, and exploratory research. It was carried out in two Family Health Strategies in a municipality in Rio Grande do Sul, Brazil. Semi-structured interviews were conducted with health workers, and thematic content analysis was used. Results: The data was organized into two categories: actions in the territory and care in freedom. And the frailties of the territory. It was noted that workers face challenges in promoting care and freedom for users, such as the fragility and setbacks of public policies. Final considerations: It is important for workers to resist setbacks and to strengthen other care strategies in the territory, promoting free and comprehensive care for users of psychoactive substances.